Avaliação de sustentabilidade ambiental do sistema de abastecimento de água e esgotamento sanitário de Uberaba - MG - Silva, Vinícius Arcanjo da (2016)
This paper analyses the sustainability under the environmental (ecological) perspective of Water Supply and Sanitary Sewers Systems from Uberaba city, MG. It was accomplished in this analysis, An Environmental Sustainability Assessment of those systems, by the means of specific sustainability indicators proposed for Uberaba, but which may be used for other simi-lar cities. To the characterization of the systems, visitations were made to the main units as well as a documental was elaborated. The definition of the level or stage of the sustainability by the indicators was made based on a literature review, on interviews with the technicians and managers of the systems and based on the characterization and observation of the system reality, being attributed to them the following classification: Non Sustainable, Low Sustaina-bility, Medium Sustainability and High Sustainability. It was verified that the indicators that have lower compatibility to the process of sustainability to the studied systems are those rela-ted to the water physical losses, to the water per capita consumption, to the electricity con-sumption and to the sludge from the water treatment plants disposal untreated into a water body, for the Water Supply System. And those ones related to the attendance with sewage treatment, to the electricity consumption and to the usage of the treated sewage, for the Sani-tary Sewers, all of them classified as Non Sustainable.